Factors Influencing the Incidence of Stunting in Toddlers in Sukamaju Village, Kadudampit Health Center Working Area, Sukabumi District - Arifin, Rani Fitriani (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: This study was to determine the effect of immunization, economic status, maternal motivation, and family support on the incidence of stunting in toddlers. Methods: The study involved 223 toddlers in Sukamaju Village, Kadudampit Health Center Working Area, Sukabumi Regency, with data collected through questionnaires and analyzed using univariate and bivariate methods, passing an ethical review. Results: There is a significant effect of immunization on the incidence of stunting (p-value, 0.031), economic status on the incidence of stunting (p-value, 0.000), maternal motivation on the incidence of stunting (p-value, 0.000), family support on the incidence of stunting (p-value, 0.000). Conclusion: There is an effect of immunization, economic status, maternal motivation, and family support on the incidence of stunting in toddlers.